Numerical Simulation and Optimization on Launching Process of an Anti-UAV Capture Gun (Dandao Xuebao/Journal of Ballistics, 2023)
To solve the increasingly serious flight problems of the low-slow-small unmanned aerial vehicle(UAV),an anti-UAV capture gun was designed by the high-low pressure launching theory. The coupled interior and external ballistic model of the anti-UAV capture gun was established. The effects of different charge weights and volumes of high-pressure chamber on the performance of launching device capturing UAV were discussed. The launching performance,portability and safety of the device were investigated by the normalized function of the muzzle velocity,the volume and mass of the device,and the peak pressure of the high-pressure chamber. The launching performance,portability and safety for different conditions were analyzed. The particle swarm optimization was used to improve the capture performance,portability and safety of the anti-UAV capture gun. The study provides a theoretical guidance for the in-depth study of anti-drone capture system.